Consumer Perception Towards Localization of MNC Fast Food Chain in Pakistan - Mehwish Channa; Adnan Pitafi; Ghazala Tunio (NAROTAMA UNIVERSITY, Indonesia, 2021)
The study tests the consumer preferences in Pakistan (a developing economy) to know about the consumer’s choice and localization of MNC to have clear understanding of entering in to the new market following the local culture of the country. Study focuses on the multinational fast food outlets. The research is grounded on both primary & secondary information and primary data is collected randomly from 412 fast food consumers through closed ended questionnaire and analyzed through simple percentage analysis and SPSS to know about the relationship with different factors like, location, Quality, consumer satisfaction and preferences. Findings show that consumer’s choice is influenced by quality, price as well as location. Study also shows that McDonalds is a high quality restaurant according to the consumers perception and more expensive than any other MNC outlet in Pakistan, consumers prefer to visit KFC and McDonalds frequently the consumers in Pakistan prefer food with the price conscious attitude. The main thing for the fast food restaurants is the food which is served quickly and finds it more advantageous. According to this study location accessibility is also a motive for consumers when they choose a particular outlet, closer restaurants are more numerous for easy take away.